2018
DOI: 10.1021/acsomega.8b00862
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Modification Promotes Catalytic Activity of a Single-Site Cobalt Heterogeneous Catalyst for Propane Dehydrogenation

Abstract: The effect of Zr modification on the catalytic activity of Co/SiO 2 was investigated for nonoxidative propane dehydrogenation. Isolated Zr on SiO 2 surface sites were prepared by organometallic synthesis using Zr(O t Bu) 4 as a precursor. The resulting Zr/SiO 2 support was functionalized with Co 2+ ions via strong electrostatic adsorption. Spectroscopic (diffuse reflecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 77 publications
3
28
0
Order By: Relevance
“…The tuning of the support TiO 2 oxygen donation ability by use of an anchoring site (e.g., ≡TiO-Zr-O − ) can be used to alter both rate and selectivity of conversion efficiency i.e., (NO x , CO, HC). Possibly Co 2+ active sites prefer to associate with ≡TiO-Zr-O − sites as compare to ≡TiO- [42,43] as shown in below Figure 10. Furthermore, zirconia promoted catalyst efficiency is attributed by the presence of zirconia that effect on redox properties through dispersion of active phases which oxidize CO more efficiently.…”
Section: Catalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The tuning of the support TiO 2 oxygen donation ability by use of an anchoring site (e.g., ≡TiO-Zr-O − ) can be used to alter both rate and selectivity of conversion efficiency i.e., (NO x , CO, HC). Possibly Co 2+ active sites prefer to associate with ≡TiO-Zr-O − sites as compare to ≡TiO- [42,43] as shown in below Figure 10. Furthermore, zirconia promoted catalyst efficiency is attributed by the presence of zirconia that effect on redox properties through dispersion of active phases which oxidize CO more efficiently.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Hydrocarbons conversion efficiency was noticed as 82.5% for simple catalyst at 1500 RPMs as shown in Figure 12 but in case of promoted catalyst HC Furthermore, the type of basic sites together with whole basicity and whole acidity of the ZrO2based catalysts also effect the HC, CO, and NOx conversion on active sites. The Lewis basic sites of ZrO2 consist of coordinately unsaturated O −2 species and the Lewis acidic sites is Zr 4+ species [42][43][44][45][46]. Overall reactions on the surface of catalysts were given below in Figure 11: Amin et al [39] developed a copper-based catalytic converter and reported that it converted HCs by 33% and CO by 66% at full load.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…[21] Co/Al 2 O 3 À NS and Co/Al 2 O 3 À NF samples shows higher intensities at the three positions whereas Co/Al 2 O 3 À NP shows lower intensity peaks with the broad band at 720 nm and 420 nm indicative of octahedral Co + 2 species. [23] The Co/ Al 2 O 3 À NS catalyst consists of Co + 2 mostly in the tetrahedral state, Co/Al 2 O 3 À NF consists of a mixture of Co + 2 in the tetrahedral and octahedral state, and Co/Al 2 O 3 À NP consists mostly of octahedral state originated from the Co 3 O 4 as a precursor with a small intensity of tetrahedral Co + 2 peaks.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…[22] This analysis will help to generate a correlation between the activity, different coordination states of cobalt, and the distinctive role of tetrahedral and octahedral coordinated Co + 2 in dehydrogenation reaction. [23]…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…Their observation that selectivities increased with decreasing Co content suggested that the selective sites are associated with isolated Co. Spectroscopic data implied that the active species was Co 2+ in a tetrahedral environment, strongly bound to the silica. Others have also shown that isolated Co can exhibit selective C-H activation of alkanes [15][16][17]. For example, Hu et al used electrostatic adsorption of monomeric hexamminecobalt (III) with low metal loadings to produce silica-supported catalysts with isolated Co [15].…”
Section: Introductionmentioning
confidence: 99%